A clinical case of atrophy of the ocular nerves associated with hypertension (Ukrainian Journal of Ophthalmology, 2026)
A clinical case of atrophy of the ocular nerves associated with hypertension
Keywords: optic nerve atrophy; clinical case; diagnosis; treatment; mistakes